Franklin D. Roosevelt and the transformation of the Supreme Court. - Shaw, Stephen K.; Pederson, William D., 1946-; Williams, Frank J. (M.E. Sharpe library of Franklin D. Roosevelt studies., 2015)
Franklin D. Roosevelt appointed 10 justices to the U.S. Supreme Court - more than any president except Washington - and during his presidency from 1933 to 1945, the Court gained more visibility, underwent greater change, and made more landmark decisions than it had in its previous 150 years of existence. This collection examines FDR's influence on the Supreme Court and the Court's growing influence on American life.